Severe cyclones and sex‐specific birth outcomes in Queensland, Australia: An interrupted time‐series analysis. Issue 1 (9th December 2022) - Parayiwa, Cynthia; Harley, David; Richardson, Alice; Behie, Alison
Abstract: Objectives: A male is less adaptable to biological stressors than a female fetus with consequent higher morbidity and mortality. Adverse birth outcomes increase and male livebirths decrease after environmental disasters, economic crises, and terrorist events. We hypothesized the ratio of male to female livebirths would decrease in areas affected by severe tropical cyclones (TCs) in Queensland, Australia. Additionally, in male livebirths, there would be an increase in preterm and low birthweight births. Lastly, we hypothesized that the pregnancy stage at which exposure occurred would modify the association between TC exposure and observed outcomes. Methods: Interrupted time series analysis was used to analyze Queensland administrative birth records from July 2007 to June 2018 for significant changes in the sex ratio at birth, measured as the proportion of male livebirths. Adjusted generalized linear models were fitted to births in areas affected by two category five TCs: cyclones Yasi (February 2011) and Marcia (February 2015). To explore male mortality and morbidity risk, additional analysis was conducted on the proportion of male stillborn, low birthweight, and preterm births. The association between estimated pregnancy stage during the TC and the proportion of male births was also analyzed. Results: Contrary to our hypothesis, increases in the proportion of male livebirths were observed following early‐pregnancy exposure to cyclone Yasi and mid‐pregnancy exposure to Marcia, although the latter was not statistically significant. No significant changes were observed in proportions of male stillborn, low birthweight, and preterm births. Conclusions: This study found a significant association between severe TCs and sex ratio at birth. The stage of pregnancy at which maternal stressors were experienced modified this association. Among people exposed in early to mid‐pregnancy, the proportion of male births was higher. This may be because of differential loss of females in utero. Studying sex differences in birth outcomes provides insight into in utero vulnerabilities associated with environmental stressors. Climate change is increasing the intensity and frequency of natural disasters. Understanding fetal vulnerability to environmental stressors will provide crucial information supporting early life health interventions that mitigate the immediate and long‐term effects.